PEMASARAN IKAN PATIN ASAP DIKOTO MASJID BANGKINANG - Novi Yona Sidratul Munti; Dwi Asril Syaifuddin; Thohar Saputro (Universitas Pahlawan Tuanku Tambusai, 2019)
Catfish Smoked is a traditional processed product in Indonesia. Several types of fish can be used as raw material for smoked fish. One of them is catfish (pangasius-pangasius). Modification of fish fogging is used to produce smoked fish that consumers like. Modificationsin the management of smoked catfish made in this study consisted of, namely, catfish models without being slashed then smoked and catfish models that were poked and smoked. In the marketing environment, whether market participants or businesses tend to change faster and more complex than in previous decades. This condition can be understood because the business world is always changing dynamically so that marketing needs to be within close proximity to consumers and know the behavior of the consumers beingserved. This situation is also driven by the globalization of trade and technological developments that are a factor in motion.